Correlation of the functional difficulties questionnaire (FDQ-9) with dynamic balance using the SMART instrumented wobbleboard. (September 2016) - Clark, C.J.; Clark, S.; Dorey, C.; Williams, J.
Abstract: Objectives: To investigate concurrent validity of the Functional Difficulties Questionnaire (FDQ-9) using balance tasks on the SMARTwobbleboard. Poor balance is associated with reduced physical activity which may impact on quality of life. There is a requirement to use simple tests to assess balance so that suitable interventions can be employed to ameliorate poor balance and enhance uptake of physical activity. Design: Observational study employing 30 healthy volunteers who completed the FDQ-9 and undertook three balance tasks on the SMARTwobbleboard: double leg stance eyes open (DLSEO); double leg stance eyes closed (DLSEC) and single leg stance eyes open (SLSEO). Results: There were moderate significant correlations between the FDQ-9 and DLSEO and SLSEO. There were significant between group differences in dynamic balance for participants with FDQ-9 ≤ 18 (indicative of no functional difficulties) and FDQ-9 ≥ 19 (indicative of one or more functional difficulties) for DLSEO and SLSEO. Conclusions: Significant moderate correlations were recorded between the FDQ-9 and the SMARTwobbleboard in healthy adults indicating a relationship between dynamic balance and questionnaire scores (DLSEO and SLSEO). Initial findings contribute to the concurrent validity of the FDQ-9 which could also be used as a simple tool for assessing balance. Highlights: Concurrent validity of the FDQ-9 was explored with the SMARTwobbleboard. Correlations between the FDQ-9 and balance tasks were reported; SLSEO; DLSEO; DLSEC. Moderate statistically significant correlations between FDQ-9 and SLSEO; DLSEO task. No correlations with the DLSEC suggesting task exceeded participant abilities. Data contributes to the concurrent validity of the FDQ-9.